Comparison of Escherichia coliBacterial ContaminationLevels in Fresh Chicken and Frozen Chicken Meat in Medan City - Manurung, Kevin Andreas; Ma'ruf Tafsin; Fuad Hasan; Wahyudi Himawan Sutanto (Jurnal Peternakan Integratif, 2025)
Chicken meat is one of the animal foods consumed because it contains high nutrients, has a delicious taste and aroma, has a soft texture and is relatively cheap. The research aims to determine the difference in the level of Escherichia coli bacterial contamination in fresh chicken meat and frozen chicken meat in Medan City. The number of samples at traditional markets was 20 samples and the number of samples at frozen chicken stalls was 20 samples. The sampling method used in the research was a survey. Data processing uses the t test and the Mann Whitney test. The research results showed that the number of colonies in traditional markets was greater than the number of colonies in frozen chicken stalls. The Maximum Microbial Contamination Limit (BMCM) of all traditional markets studied all exceeded the BMCM, and the Maximum Bacterial Contamination Limit (BMCM) of all frozen chicken stalls studied did not all exceed the BMCM (SNI 01-7388-2009). The percentage level of Escherichia coli bacterial contamination in traditional markets is 100% and the percentage of bacterial contamination in frozen chicken stalls is 30%. In conclusion meat that comes from frozen chicken stalls is better because it has bacterial contamination below the Maximum Microbial Contamination Limit (BMCM) so it is safer for public consumption than from traditional markets